Detector de luminescência de descargas eletrocirúrgicas - Góes, Sandro Waldir (2016)
The electrosurgical procedure, used in large surgeries, promotes cut and/or coagulation of the organic tissue. This procedure is possible because the electrical discharge between a metal electrode and the organic tissue. Characteristics of the spark are still almost unknown. This work intends to collaborate to the electrosurgical sparks study, reporting the development of a photodetector device, capable to detect flashes of light in hundreds of kHz, and introducing the waveform of luminescence from the electrosurgical discharge. Methods: The photodetector deviceis composed mainly of a photodiode PIN and an transimpedance amplifier. Spacial care has taken to isolate the device from electromagnetic noise, employing a shield and an optical fiber cable. To obtain, analyze and store data, a specific hardware, software and techniques, have been used and described in detail. Results: From the luminescence signal detected by photodetector device and voltage and current shapes stored in an oscilloscope, it is possible to see the relation between sparks luminescence, voltage and current on positive and negative cycles of the electrical discharge. The luminescence collaborates to show the asymmetry on voltage signals already reported by other researchers. Conclusion: Effective for the study of luminescence emitted by electrosurgical discharges, enabling a new study of the same channel, particularly the speed of response.